(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
In this article, devoted to the influence of reason on the cognitive development of a child, as well as the role of knowledge in the acquisition of knowledge, special attention is paid to the mental ontogenesis of primary school children.